2022
DOI: 10.1038/s43018-022-00366-1
|View full text |Cite
|
Sign up to set email alerts
|

IKAROS and MENIN coordinate therapeutically actionable leukemogenic gene expression in MLL-r acute myeloid leukemia

Abstract: Acute myeloid leukaemia (AML) remains difficult to treat and requires new therapeutic approaches. Potent inhibitors of the chromatin-associated protein MENIN have recently entered human clinical trials, opening new therapeutic opportunities for some genetic subtypes of this disease. Using genome-scale functional genetic screens we identified IKZF1 /IKAROS as an essential transcription factor in MLL1-rearranged ( MLL - r ) AML that maintains l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 91 publications
1
18
0
1
Order By: Relevance
“…S3J and S3K) [10]. We also confirmed that IKAROS (encoded by IKZF1) is a dependency in KMT2A (MLL1)rearranged (MLL1-r) and mtNPM1-expressing AML cells [15], by demonstrating that CRISPR knockout of IKZF1 significantly increased sensitivity of OCI-AML3 cells to ziftomenib (Supplementary Figs. S4A and S4B).…”
Section: To the Editorsupporting
confidence: 75%
“…S3J and S3K) [10]. We also confirmed that IKAROS (encoded by IKZF1) is a dependency in KMT2A (MLL1)rearranged (MLL1-r) and mtNPM1-expressing AML cells [15], by demonstrating that CRISPR knockout of IKZF1 significantly increased sensitivity of OCI-AML3 cells to ziftomenib (Supplementary Figs. S4A and S4B).…”
Section: To the Editorsupporting
confidence: 75%
“…Among them, IKZF1 N159S was a recurrent hotspot mutation, which closely clustered in a subset of patients with myelodysplasia‐related mutations and upregulated gene expression of the HOXA / B family genes 14 . Notably, immunomodulatory drugs inducing IKAROS protein degradation showed potential therapeutic efficiency in the HOXA ‐related AML, which suggests the emerging synergistic role of IKAROS in high‐risk AML 27 …”
Section: Introductionmentioning
confidence: 98%
“…14 Notably, immunomodulatory drugs inducing IKAROS protein degradation showed potential therapeutic efficiency in the HOXA-related AML, which suggests the emerging synergistic role of IKAROS in high-risk AML. 27 To date, a few critical issues remain to be addressed to further explore the pathogenesis and improve the prognosis of AML patients with IKZF1 mutations. Firstly, genetic alterations of IKZF1 are common and widely reported in B-ALL, however, the genomic landscape, molecular classification and clinical significance are scarcely investigated in a large AML cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, combined Menin- and FLT3 inhibition had synergistic effects in KMT2A -rearranged and NPM1c leukemia [57,58]. Apart from that, combined degradation of the transcription factor Ikaros (IKZF) by mezigdomide treatment and Menin inhibition has shown synergistic effects in preclinical AML models [59,60 ▪ ].…”
Section: Preventing and Overcoming Resistance To Menin Inhibition Wit...mentioning
confidence: 97%